A method for reducing fluorine impurity in phosphogypsum
By mixing phosphogypsum with quicklime and using modified carbon powder to adsorb impurity fluorine, the problem of introducing new impurities and large water consumption in the prior art is solved, and the efficient and environmentally friendly removal effect of impurity fluorine in phosphogypsum is achieved. .
Patent Information
- Application Number
- CN202311053996.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-21
AI Technical Summary
In the prior art, when treating impurities fluorine in phosphogypsum, there are problems of introducing new impurities and large water consumption, making it difficult to achieve environmentally friendly and efficient removal effects.
By mixing phosphogypsum with quicklime, diluting it into mineral slurry with water, and preparing modified carbon powder using straw, livestock manure and iron oxide modifier, adsorbing the impurity fluorine in the phosphogypsum to reduce the amount of water.
It is achieved to effectively reduce the content of impurities in phosphogypsum without introducing a large amount of impurities, improve the purity of phosphogypsum, reduce the amount of water, and meet the requirements of low-carbon environmental protection.
Smart Images

Figure BDA0004405450540000041 
Figure BDA0004405450540000042 
Figure BDA0004405450540000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial solid waste treatment and disposal, and specifically relates to a method for reducing impurity fluorine in phosphogypsum. Background Art
[0002] Phosphogypsum is a solid waste produced in the production process of wet phosphoric acid. Its main component is calcium sulfate dihydrate, which can be used for building materials, decoration, fertilizer, soil improvement and water purification. The composition of industrially produced phosphogypsum is relatively complex. In addition to calcium sulfate dihydrate, there are also incompletely decomposed phosphate ore, residual phosphoric acid, fluoride, acid insoluble matter, organic matter, etc. Among them, the presence of fluorine and organic matter has the greatest impact on the resource utilization of phosphogypsum. If not handled properly, it will cause harm to the environment, plants and human health. Therefore, in the process of recycling and reusing phosphogypsum, it must be operated in strict accordance with the requirements and standards; at the same time, some effective technical means should be used to purify and treat phosphogypsum to reduce the content of toxic and harmful components, so as to better promote the recycling and utilization of phosphogypsum.
[0003] CN112871457A discloses a method for purifying and removing impurities from phosphogypsum, which comprises adding water to phosphogypsum to prepare a slurry, adding quicklime to precipitate soluble phosphorus and fluorine, then adding water glass under strong stirring to disperse the generated phosphorus and fluorine precipitates with gypsum, and then adding a decolorizing agent and an adsorbent agent to finally obtain a gypsum concentrate. The phosphogypsum sample obtained by this method has improved whiteness and lower soluble phosphorus and fluorine contents, but because a large amount of agents need to be added in the process flow, the process cost is high, and the agents themselves have a certain influence on the properties of the phosphogypsum, increasing the uncertainty of the gypsum quality.
[0004] CN106977123A discloses a citric acid and water washing process for removing fluorine impurities from phosphogypsum, in which citric acid water is added to phosphogypsum for washing, and then the phosphogypsum sample is washed, and finally the impurities are removed and dried by a washing process. This scheme uses lime and water to wash the phosphogypsum sample, which will bring soluble impurities in quicklime into the phosphogypsum, causing secondary pollution, and the phosphogypsum in the scheme needs to be washed multiple times, and the water consumption is large, which does not meet the requirements of green environmental protection.
[0005] Adding quicklime to phosphogypsum can effectively convert soluble phosphorus and fluorine into insoluble impurities, but how to remove impurities without introducing new impurities has become a hot issue in this field. On the one hand, conventional methods have the problem of introducing new impurities resulting in uncertain quality of phosphogypsum, and on the other hand, they have the problems of high water consumption and environmental pollution. Therefore, how to explore an environmentally friendly phosphogypsum treatment method that introduces less impurities has become a common goal in this field. Summary of the invention
[0006] In view of the above technical problems, the present invention provides a method for reducing the impurity fluorine in phosphogypsum, using quicklime to neutralize the acidity of phosphogypsum, preparing modified carbon powder through straw, livestock manure and iron oxide modifier, and adsorbing the impurity fluorine in phosphogypsum to achieve better fluorine reduction effect, effectively improve the purity of phosphogypsum, and reduce the amount of water used, which is helpful to promote the recycling and reuse of phosphogypsum.
[0007] In order to achieve the above object, the present invention provides a method for reducing the impurity fluorine in phosphogypsum, comprising the following steps:
[0008] (1) mixing phosphogypsum and quicklime in proportion to obtain a mixture;
[0009] (2) adding water to the mixture to dilute it to obtain a slurry, stirring it for 1-2 hours and then letting it stand for 3-4 days;
[0010] (3) weighing straw, livestock manure and modifier in proportion, mixing them evenly, calcining them at 450-550° C. for 2-3 h, washing them with water 2-3 times after cooling, and crushing them to 1 mm after drying to obtain modified carbon powder;
[0011] (4) adding the dried modified carbon powder to the aged slurry obtained in step (1), stirring evenly and then allowing to stand for 3-4 days;
[0012] (5) After aging, the supernatant is discarded to obtain fluoride-reduced phosphogypsum.
[0013] Preferably, the mass ratio of the phosphogypsum to quicklime in step (1) is 100-110:1-3.
[0014] Further preferably, the phosphogypsum is a by-product in the preparation process of industrial wet phosphoric acid, and the content of calcium sulfate dihydrate is 30-35%.
[0015] Preferably, the slurry concentration in step (2) is 40-50%, and the pH of the slurry is 6-8.
[0016] Preferably, the straw in step (3) is any two of rice straw, wheat straw, corn straw, soybean straw and peanut shell, with a mass ratio of 1:1.
[0017] Further preferably, the straw is corn straw and peanut shell.
[0018] Preferably, the livestock manure in step (3) is cow manure or pig manure; and the modifier is iron oxide.
[0019] Preferably, the mass ratio of the straw, livestock manure and modifier in step (3) is 40-60:10-15:3-5.
[0020] Preferably, the mass ratio of phosphogypsum to modified carbon powder in the slurry of step (4) is 100-110:53-80.
[0021] The beneficial effects of the present invention are:
[0022] 1. Modified carbon powder is prepared by using organic carbon-rich materials such as straw and livestock manure, and adding iron oxide as a modifier. The adsorption performance of biochar is improved by compounding biochar and modifying iron oxide. It can effectively adsorb impurities in phosphogypsum. At the same time, after the adsorption is completed, it will not introduce a large amount of impurities. It can not only be used for phosphogypsum impurity removal, but also can be used in industrial impurity removal and water purification.
[0023] 2. Mix quicklime and phosphogypsum in proportion, add water to dilute into slurry, use quicklime to neutralize the acidity of phosphogypsum, and increase the Ca content in the solution. 2+ Ion concentration promotes the water-soluble fluorine in phosphogypsum to generate inert and insoluble calcium fluoride precipitation. The reaction equation is: Ca 2+ +2F - →CaF2↓. After quicklime is added, it not only neutralizes the acidic environment of phosphogypsum, but also increases the Ca 2+ concentration, which promotes the formation of calcium fluoride precipitation, and the neutral or weakly acidic phosphogypsum is more in line with the requirements and characteristics of its comprehensive utilization, which helps to promote the comprehensive utilization of phosphogypsum.
[0024] 3. Utilize the strong adsorption capacity of modified carbon powder to adsorb the impurity fluorine in the phosphogypsum slurry after quicklime treatment, purify the phosphogypsum, and reduce the content of impurity fluorine in the phosphogypsum. The modified carbon powder added without generating excess waste can be used as raw material, and the phosphogypsum can be reused in the subsequent use of waste production, soil improvement or water purification, thereby reducing the impact on the components of the phosphogypsum.
[0025] 4. The present invention is simple to operate, low in cost, high in efficiency in removing impurity fluorine, and has readily available raw materials. It uses less water and the process water can be recycled after being treated, which reduces water consumption and meets the requirements of low-carbon and environmental protection. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.
[0027] Example 1
[0028] In order to explore which organic carbon-rich substances have better impurity fluorine adsorption effect after carbonization, the main types of crop straw in my country were selected: rice straw, wheat straw, corn straw, soybean straw, peanut shells and some widely raised livestock manure: pig manure, cow manure, etc. The adsorption effect after carbonization is as follows:
[0029] (1) Weigh 100 g of straw or livestock manure, place it in a high-temperature reactor for carbonization, heat it to 500°C, react for 120 min, and then cool it;
[0030] (2) The powder after the reaction was washed with tap water three times to remove oily substances and water-soluble impurities, and then ground into 1 mm after drying to obtain different types of carbon powder;
[0031] (3) Prepare a sodium fluoride solution with a concentration of 20 mg / L, 100 mL per group, add 1 g of each type of carbon powder, use an oscillator at 300 rpm, oscillate and adsorb for 1 hour, filter and detect the fluoride ion content in the filtrate. The test results are shown in Table 1:
[0032] Table 1 Experimental data of adsorption kinetics of different types of carbon powder
[0033]
[0034] The experimental results show that among the above-mentioned carbon powders, the carbon powder obtained after high-temperature carbonization of three organic carbon-rich substances, corn straw, peanut shells and cow dung, has a better adsorption effect on fluoride ions. Therefore, in subsequent experiments, these three substances were selected for carbonization treatment and adsorption experiments were carried out on the impurity fluorine in phosphogypsum.
[0035] Example 2
[0036] In order to explore the optimal combination ratio of carbon powder obtained by high-temperature carbonization of three organic carbon-rich materials, corn stalks, peanut shells and cow dung, so as to achieve the best adsorption effect, the three carbon powders were orthogonally combined, and the carbon powder added in each combination was added in equal mass ratio to explore the adsorption effect of fluoride ions after the combination. The test results are shown in Table 2:
[0037] Table 2 Orthogonal experimental data of adsorption kinetics of three carbon powders: corn straw, peanut shell and cow dung
[0038]
[0039]
[0040] The experimental results show that the orthogonal results of the three carbon powders of corn straw, peanut shells and cow dung show that after the three carbon powders are mixed in pairs, their adsorption effects on fluoride ions are better than those of single carbon powder. Among them, the adsorption effect is best after the three carbon powders are mixed, and the fluoride ion removal rate reaches 98%.
[0041] Example 3
[0042] In order to clarify the effect of adding carbon powder on reducing the impurity fluorine in phosphogypsum, corn straw, peanut shells and cow dung were mixed to prepare carbon powder and added to phosphogypsum to explore the effect of carbon powder on the pH value and impurity fluorine content of phosphogypsum samples. The specific steps are as follows:
[0043] (1) The phosphogypsum sample is mixed evenly with quicklime in a mass ratio of 100:1, that is, 100 parts of phosphogypsum are mixed with 1 part of quicklime, and then diluted with an appropriate amount of water to form a slurry to a slurry concentration of 50%;
[0044] (2) detecting the pH value of the slurry obtained in step (1) and adjusting the pH value of the reaction system to between 6 and 8 using quicklime, stirring evenly to promote precipitation reaction, and allowing to stand for aging for 3 days;
[0045] (3) 20 parts of corn stalks, 20 parts of peanut shells, and 20 parts of cow dung were mixed evenly, placed in a high-temperature reactor, reacted at 500° C. for 120 min, cooled to room temperature, washed with water to remove ash, dried, and crushed to 1 mm to obtain mixed carbon powder;
[0046] (4) adding the mixed carbon powder prepared in step (3) to the slurry aged in step (2), stirring evenly, and allowing to stand for 3 days;
[0047] (5) The supernatant of the slurry after aging in step (4) is discarded to obtain fluorine-reduced phosphogypsum, and its pH value and impurity fluorine content are measured. The results are shown in Table 3.
[0048] Example 4
[0049] In order to clarify the effect of not adding carbon powder on reducing the impurity fluorine in phosphogypsum, only quicklime was added to the phosphogypsum without adding carbon-rich adsorbent, and the pH value and impurity fluorine content in the phosphogypsum were tested. The specific steps are as follows:
[0050] (1) The phosphogypsum sample is mixed evenly with quicklime in a mass ratio of 100:1, that is, 100 parts of phosphogypsum are mixed with 1 part of quicklime, and then diluted with an appropriate amount of water to form a slurry to a slurry concentration of 50%;
[0051] (2) detecting the pH value of the slurry obtained in step (1) and adjusting the pH value of the reaction system to between 6 and 8 using quicklime, stirring evenly to promote precipitation reaction, and allowing to stand for 6 days;
[0052] (3) The supernatant of the slurry after aging in step (2) was discarded to obtain fluorine-reduced phosphogypsum, and its pH value and impurity fluorine content were measured. The results are shown in Table 3.
[0053] Table 3 pH value and fluorine content index of phosphogypsum samples with or without carbon powder addition
[0054] project Blank control Example 3 Example 4 pH 3.24 5.93 5.47 Water-soluble fluorine content (ppm) 612 78 425 Total fluorine content (ppm) 3621 3329 3619
[0055] The blank control in Table 3 is an untreated phosphogypsum sample. From the above experimental data, it can be seen that the pH value of the phosphogypsum sample to which quicklime and carbon powder are added in Example 3 is 5.93, which is weakly acidic, and the water-soluble fluorine content is reduced by about 87.25% and the total fluorine content is reduced by about 8.06% compared with the control, indicating that Example 3 can effectively reduce the water-soluble fluorine content in the phosphogypsum, but has little effect on the total fluorine of the phosphogypsum sample; the pH value of the phosphogypsum sample to which only quicklime is added without adding mixed carbon powder in Example 4 is 5.47, which is weakly acidic, and the water-soluble fluorine content is reduced compared with the untreated phosphogypsum sample. In Example 4, the water-soluble fluorine content of the group treated with only quicklime is 425ppm, which is about 30.56% lower than that of the blank treatment, and the total fluorine content is 3619ppm, which is not significantly changed compared with Example 4, indicating that the acidity of the phosphogypsum can be neutralized to a certain extent by adding only quicklime without adding mixed carbon powder, but the fluorine reduction and impurity removal effect is poor.
[0056] Example 5
[0057] In order to clarify the effect of carbon powder modification on reducing the impurity fluorine in phosphogypsum, the mixed carbon powder was modified with iron oxide, and the effects of unmodified carbon powder and modified carbon powder on the pH value and impurity fluorine content of phosphogypsum samples were compared. The specific steps are as follows:
[0058] (1) The phosphogypsum sample is mixed evenly with quicklime in a mass ratio of 100:1, that is, 100 parts of phosphogypsum are mixed with 1 part of quicklime, and then diluted with an appropriate amount of water to form a slurry to a slurry concentration of 50%;
[0059] (2) detecting the pH value of the slurry obtained in step (1) and adjusting the pH value of the reaction system to between 6 and 8 using quicklime, stirring evenly to promote precipitation reaction, and allowing to stand for aging for 3 days;
[0060] (3) 20 parts of corn stalks, 20 parts of peanut shells, 20 parts of cow dung, and 3 parts of iron oxide were mixed evenly, placed in a high-temperature reactor, reacted at 500° C. for 120 min, cooled to room temperature, washed with water to remove ash, dried, and crushed to 1 mm to obtain modified carbon powder;
[0061] (4) adding the modified carbon powder obtained in step (3) to the phosphogypsum slurry aged in step (2), stirring evenly, and standing and aging for 3 days;
[0062] (5) The supernatant waste liquid of the slurry obtained in step (4) was discarded to obtain fluorine-reduced phosphogypsum, and its pH value and impurity fluorine content were measured. The results are shown in Table 4:
[0063] Table 4 pH value and fluorine content index of phosphogypsum samples in carbon powder modification or not
[0064] project Blank control Example 3 Example 5 pH 3.24 5.93 6.23 Water-soluble fluorine content (ppm) 612 78 46 Total fluorine content (ppm) 3621 3329 3282
[0065] From the above experimental data, it can be seen that the pH value of the phosphogypsum sample treated with the modified carbon powder prepared by iron oxide in Example 5 is 6.23, which is weakly acidic, weaker than that of Example 3, and the water-soluble fluorine content is only 46 ppm, which is about 42.11% lower than that of Example 3 and about 92.48% lower than that of the blank control. The total fluorine content is 3282 ppm, which is about 1.41% lower than that of Example 3 and about 9.42% lower than that of the blank control, indicating that the phosphogypsum sample treated with unmodified carbon powder has a certain degree of improvement in acid neutralization and adsorption of impurity fluorine compared with the phosphogypsum sample treated with quicklime alone, but the phosphogypsum sample treated with modified carbon powder has significantly improved acid neutralization and adsorption of impurity fluorine, indicating that the modified carbon powder obtained after modification with iron oxide has significantly improved adsorption performance and acid neutralization performance, and can be used to reduce the impurity fluorine content of phosphogypsum.
[0066] Example 6
[0067] In order to clarify the effect of the order of adding quicklime and modified carbon powder on reducing the impurity fluorine in phosphogypsum, the order of adding quicklime and modified carbon powder was adjusted. The specific steps are as follows:
[0068] (1) 20 parts of corn stalks, 20 parts of peanut shells, 20 parts of cow dung, and 3 parts of iron oxide were mixed evenly, placed in a high-temperature reactor, and reacted at 500° C. for 120 min. The obtained modified carbon powder was washed with water to remove ash, dried, and crushed to 1 mm for later use;
[0069] (2) adding the modified carbon powder obtained in step (1) to 100 parts of phosphogypsum samples, adding water to a slurry concentration of 50%, stirring thoroughly and then standing for aging for 3 days;
[0070] (3) Add 1 part of quicklime to the phosphogypsum slurry obtained in step (2), stir thoroughly and allow to stand for 3 days.
[0071] (4) After aging, the supernatant was discarded to obtain a phosphogypsum sample after defluorination treatment, and its pH value and impurity fluorine content were measured. The results are shown in Table 5:
[0072] Table 5 Effect of the order of adding quicklime and modified carbon powder on the pH value and fluorine content of phosphogypsum samples
[0073]
[0074]
[0075] The results show that the pH value of the phosphogypsum sample obtained by first adding modified carbon powder and then adding quicklime in Example 6 is 5.94, which is lower than the pH value of Example 5. The water-soluble fluorine content is 70 ppm, which is 34.29% higher than that of Example 5. The total fluorine content is 3392, which is 3.24% higher than that of Example 5. This shows that when using modified carbon powder and quicklime to treat phosphogypsum, quicklime should be used first to convert the soluble fluorine in the phosphogypsum into insoluble fluorine as much as possible, and then the modified carbon powder is added to absorb the impurity fluorine by its adsorption effect, thereby reducing the content of impurity fluorine in the phosphogypsum as much as possible and further neutralizing the acidic substances therein.
[0076] Example 7
[0077] In order to clarify the effect of quicklime addition and pH value of the reaction system on reducing the impurity fluorine in phosphogypsum, the following experiment was designed:
[0078] (1) The phosphogypsum sample was mixed evenly with quicklime in a mass ratio of 100:3, that is, 100 parts of phosphogypsum were mixed with 3 parts of quicklime, and then diluted with an appropriate amount of water to form a slurry to a slurry concentration of 50%;
[0079] (2) detecting the pH value of the slurry obtained in step (1) and adjusting the pH value of the reaction system to between 6 and 8 using quicklime, stirring evenly to promote precipitation reaction, and allowing to stand for aging for 3 days;
[0080] (3) 20 parts of corn stalks, 20 parts of peanut shells, 20 parts of cow dung, and 3 parts of iron oxide were mixed evenly, placed in a high-temperature reactor, reacted at 500° C. for 120 min, cooled to room temperature, washed with water to remove ash, dried, and crushed to 1 mm to obtain modified carbon powder;
[0081] (4) adding the modified carbon powder obtained in step (3) to the phosphogypsum slurry aged in step (2), stirring evenly, and standing and aging for 3 days;
[0082] (5) The supernatant waste liquid of the slurry obtained in step (4) was discarded to obtain fluorine-reduced phosphogypsum, and its pH value and impurity fluorine content were measured. The results are shown in Table 6:
[0083] Table 6 pH value and fluorine content index of phosphogypsum samples after changing the amount of quicklime
[0084] project Blank control Example 5 Example 7 pH 3.24 6.23 8.57 Water-soluble fluorine content (ppm) 612 46 104 Total fluorine content (ppm) 3621 3282 3443
[0085] From the above experimental data, it can be seen that after changing the amount of quicklime and the pH value of the reaction system, the pH value in the phosphogypsum sample is 8.57, which is weakly alkaline, and the water-soluble fluorine content is significantly lower than that of the untreated phosphogypsum sample, the water-soluble fluorine content is 104 ppm, which is about 83.01% lower than that in Example 4, and the total fluorine content is 3443 ppm, which is about 4.92% lower than that in Example 4; compared with Example 5, the pH of Example 7 is higher, the water-soluble fluorine content increases by 55.77%, and the total fluorine content increases by 4.68%, indicating that an efficient and environmentally friendly method for removing impurity fluorine in phosphogypsum has a better fluorine reduction effect in a neutral and slightly acidic environment, and under slightly alkaline conditions, the fluorine reduction effect is worse than that under neutral and slightly acidic conditions.
[0086] Example 8
[0087] In order to clarify the effect of the addition amount of modified carbon powder on reducing the impurity fluorine in phosphogypsum, the following experiment was designed:
[0088] (1) The phosphogypsum sample is mixed evenly with quicklime in a mass ratio of 100:1, that is, 100 parts of phosphogypsum are mixed with 1 part of quicklime, and then diluted with an appropriate amount of water to form a slurry to a slurry concentration of 50%;
[0089] (2) detecting the pH value of the slurry obtained in step (1) and adjusting the pH value of the reaction system to between 6 and 8 using quicklime, stirring evenly to promote precipitation reaction, and allowing to stand for aging for 3 days;
[0090] (3) 40 parts of corn stalks, 40 parts of peanut shells, 40 parts of cow dung and 6 parts of iron oxide were mixed evenly, placed in a high-temperature reactor, and reacted at 500° C. for 120 min to obtain modified carbon powder, which was then washed with water to remove ash, dried and crushed to 1 mm for later use.
[0091] (4) adding the modified carbon powder obtained in step (3) to the slurry aged in step (2), stirring evenly, and allowing to stand for 3 days;
[0092] (5) The supernatant waste liquid of the slurry obtained in step (4) was discarded to obtain fluorine-reduced phosphogypsum, and its pH value and impurity fluorine content were measured. The results are shown in Table 7:
[0093] Table 7 pH value and fluorine content index of phosphogypsum samples after changing the amount of modified carbon powder
[0094] project Blank control Example 5 Example 8 pH 3.24 6.23 6.46 Water-soluble fluorine content (ppm) 612 46 42 Total fluorine content (ppm) 3621 3282 3247
[0095] It can be seen from the above experimental data that after the amount of modified carbon powder is increased from 63 parts (20 parts of corn stalks, 20 parts of peanut shells, 20 parts of cow dung, and 3 parts of iron oxide) to 126 parts (40 parts of corn stalks, 40 parts of peanut shells, 40 parts of cow dung, and 6 parts of iron oxide), the pH value of the treated phosphogypsum sample is 6.46, which is 0.23 higher than that in Example 5, more neutral, and the water-soluble fluorine content is also reduced by 4ppm, and the total fluorine content is also reduced to 3247ppm, but there is no significant difference, indicating that when the amount of modified carbon powder is doubled, there is no significant difference in the reduction of impurity fluorine in the phosphogypsum sample and the fluorine reduction effect of the unadjusted amount, indicating that the amount of carbon powder and modifier in an efficient and environmentally friendly method for removing impurity fluorine in phosphogypsum has reached saturation, and further increasing the amount cannot further reduce the impurity fluorine content in the phosphogypsum.
[0096] Example 9
[0097] In order to clarify the effect of reaction volume on reducing the impurity fluorine in phosphogypsum, the reaction volume was changed by adjusting the amount of water. The specific steps are as follows:
[0098] (1) The phosphogypsum sample was mixed evenly with quicklime in a mass ratio of 100:1, that is, 100 parts of phosphogypsum were mixed with 1 part of quicklime, and then diluted with an appropriate amount of water to form a slurry to a slurry concentration of 20%;
[0099] (2) detecting the pH value of the slurry obtained in step (1) and adjusting the pH value of the reaction system to between 6 and 8 using quicklime, stirring evenly to promote precipitation reaction, and allowing to stand for aging for 3 days;
[0100] (3) 20 parts of corn stalks, 20 parts of peanut shells, 20 parts of cow dung and 3 parts of iron oxide were mixed evenly, placed in a high-temperature reactor, and reacted at 500° C. for 120 min to obtain modified carbon powder, which was then washed with water to remove ash, dried and crushed to 1 mm for later use.
[0101] (4) adding the modified carbon powder obtained in step (3) to the slurry aged in step (2), stirring evenly, and allowing to stand for 3 days;
[0102] (5) The supernatant waste liquid of the slurry obtained in step (4) was discarded to obtain fluorine-reduced phosphogypsum, and its pH value and impurity fluorine content were measured. The results are shown in Table 8:
[0103] Table 8 pH value and fluorine content index of phosphogypsum samples after increasing the reaction volume
[0104] project Blank control Example 5 Example 9 pH 3.24 6.23 5.86 Water-soluble fluorine content (ppm) 612 46 57 Total fluorine content (ppm) 3621 3282 3463
[0105] It can be seen from the above experimental data that when the amount of water is increased and the slurry concentration is reduced from 50% to 20%, the pH value of phosphogypsum decreases from 6.23 to 5.86, which is weakly acidic, the water-soluble fluorine content increases to 57ppm, and the total fluorine content increases to 3463ppm, indicating that after increasing the reaction volume, the fluorine reduction effect is slightly worse than that under the condition of 50% slurry concentration, indicating that the optimal reaction slurry concentration for removing fluorine impurities in phosphogypsum is 50%.
[0106] Comparative Example 1
[0107] (1) The phosphogypsum sample is mixed evenly with quicklime in a mass ratio of 100:1, that is, 100 parts of phosphogypsum are mixed with 1 part of quicklime, and then diluted with an appropriate amount of water to form a slurry to a slurry concentration of 50%;
[0108] (2) detecting the pH value of the slurry obtained in step (1) and adjusting the pH value of the reaction system to between 6 and 8 using quicklime, stirring evenly to promote precipitation reaction, and allowing to stand for aging for 3 days;
[0109] (3) 20 parts of corn stalks, 20 parts of peanut shells, and 20 parts of cow dung were mixed evenly, placed in a high-temperature reactor, reacted at 500°C for 120 minutes, cooled to room temperature and crushed to 1 mm, then added to a 6 mol / L FeCl3 solution, stirred and mixed evenly, the solution pH was adjusted to 7, allowed to stand for 1 hour and then filtered 5 times, and finally the precipitate was placed in a 75°C oven to dry to obtain modified carbon powder;
[0110] (4) adding the modified carbon powder obtained in step (3) to the phosphogypsum slurry aged in step (2), stirring evenly, and standing and aging for 3 days;
[0111] (5) The supernatant waste liquid of the slurry obtained in step (4) was discarded to obtain fluorine-reduced phosphogypsum, and its pH value and impurity fluorine content were measured. The results are shown in Table 9:
[0112] Table 9 pH value and fluorine content index of phosphogypsum samples after different carbon powder modification methods
[0113] project Blank control Example 3 Example 5 Comparative Example 1 Toner No toner Mixed Toner Iron oxide modified carbon powder Ferric chloride modified carbon powder pH 3.24 5.93 6.23 6.12 Water-soluble fluorine content (ppm) 612 78 46 67 Total fluorine content (ppm) 3621 3329 3282 3297
[0114] It can be seen from the above experimental data that after treatment with ferric chloride modified carbon powder, the pH value of the phosphogypsum sample is 6.12, which is weakly acidic and slightly lower than that in Example 5; the water-soluble fluorine content is 67 ppm, which is about 89.05% lower than that of the blank control and about 45.65% higher than that of Example 5; the total fluorine content is 3297 ppm, which is about 8.95% lower than that of the blank control and has no significant change compared with Example 5. The above results show that after treatment of phosphogypsum with ferric chloride modified carbon powder, the water-soluble fluorine content in phosphogypsum can be significantly reduced compared with the blank control, but compared with the iron oxide modified carbon powder treatment group, the water-soluble fluorine content in phosphogypsum is increased, indicating that the adsorption effect of iron oxide modified carbon powder on water-soluble fluorine in phosphogypsum is better than that of ferric chloride modified carbon powder, so the present invention adopts iron oxide modified carbon powder for adsorption treatment.
Claims
1. A method for reducing the impurity fluorine in phosphogypsum, characterized in that: The following steps are involved: (1) mixing phosphogypsum and quicklime in proportion to obtain a mixture; (2) Add water to the mixture to dilute it to obtain a slurry, stir it for 1-2 hours, and then let it stand for 3-4 days; (3) Weigh straw, livestock manure and modifier in proportion, mix well and calcine at 450-550°C for 2-3h, wash with water 2-3 times after cooling, dry and crush to 1mm to obtain modified carbon powder; (4) adding the dried modified carbon powder to the aged slurry obtained in step (1), stirring evenly and then allowing to stand for 3-4 days; (5) After aging, the supernatant is discarded to obtain fluoride-reduced phosphogypsum; The straw in step (3) is any two of rice straw, wheat straw, corn straw, soybean straw and peanut shell, with a mass ratio of 1:1; and the modifier is iron oxide.
2. A method for reducing fluorine impurity in phosphogypsum according to claim 1, characterized in that: The mass ratio of the phosphogypsum to quicklime in step (1) is 100-110:1-3.
3. A method for reducing fluorine impurity in phosphogypsum according to claim 2, characterized in that: The phosphogypsum is a by-product in the preparation of industrial wet phosphoric acid, and the content of calcium sulfate dihydrate is 30-35%.
4. A method for reducing fluorine impurity in phosphogypsum according to claim 1, characterized in that: The slurry concentration in step (2) is 40-50%, and the pH of the slurry is 6-8.
5. A method for reducing fluorine impurity in phosphogypsum according to claim 1, characterized in that: The straws are corn straws and peanut shells.
6. A method for reducing fluorine impurity in phosphogypsum according to claim 1, characterized in that: The livestock manure in step (3) is cow manure or pig manure.
7. A method for reducing fluorine impurity in phosphogypsum according to claim 1, characterized in that: The mass ratio of the straw, livestock manure and modifier in step (3) is 40-60:10-15:3-5.
8. The method for reducing the fluorine impurity in phosphogypsum according to claim 1, characterized in that: The mass ratio of phosphogypsum to modified carbon powder in the slurry of step (4) is 100-110:53-80.
Citation Information
Patent Citations
Citric acid with water washing technological method for removing fluorine impurity in phosphogypsum
CN106977123A
Method for purifying and impurity removing of ardealite
CN112871457A
Preparation method of modified biochar and modified biochar
CN113145076A